Выбор сечений электрических проводов и кабелей в цепях устройств высоковольтной сильноточной импульсной техники - Баранов, М.И. (Електротехніка і електромеханіка, 2018)
Приведены результаты разработанного обобщенного электротехнического подхода к расчетному выбору по условию
термической стойкости предельно допустимых сечений SCil электрических неизолированных проводов, а также изолированных проводов и кабелей с поливинилхлоридной (ПВХ), резиновой (Р) и полиэтиленовой (ПЭТ) изоляцией с медными (алюминиевыми) жилами (оболочками), по которым в цепях высоковольтной сильноточной импульсной техники (ВСИТ) протекает аксиальный импульсный ток ip(t) с произвольными амплитудно-временными параметрами
(АВП). На основании данного подхода продемонстрированы результаты конкретного выбора сечений SCil для указанных электрических проводов (кабелей) силовых цепей ВСИТ с импульсным током, АВП которого с амплитудами
Imp=(0,1-1000) кА изменяются по апериодическому закону или закону затухающей синусоиды в нано-, микро- и миллисекундному временных диапазонах. Представлены результаты расчетной оценки предельно допустимых плотностей
δCil импульсного тока ip(t) рассматриваемых временных форм в указанных электрических проводах и кабелях силовых
цепей ВСИТ. Полученные результаты будут способствовать повышению электротермической стойкости электрических неизолированных проводов, а также изолированных проводов и кабелей с ПВХ, Р и ПЭТ изоляцией, широко
применяемых в силовых цепях ВСИТ Надані результати розробленого узагальненого електротехнічного підходу до розрахункового вибору по умові термічної стійкості гранично допустимих перерізів SCil електричних неізольованих проводів, а також ізольованих проводів і
кабелів з полівінілхлоридною (ПВХ), гумовою (Г) і поліетиленовою (ПЕТ) ізоляцією з мідними (алюмінієвими) жилами
(оболонками), по яким в колах високовольтної сильнострумної імпульсної техніки (ВСІТ) протікає аксіальний імпульсний струм ip(t) з довільними амплітудно-часовими параметрами (АЧП). На підставі даного підходу продемонстровані результати конкретного вибору перерізів SCil для вказаних електричних проводів (кабелів) силових кіл ВСІТ з імпульсним струмом, АЧП якого з амплітудами Imp=(0,1-1000) кА змінюються по аперіодичному закону або закону затухаючої синусоїди в нано-, мікро- і мілісекундному часових діапазонах. Представлені результати розрахункової оцінки
гранично допустимої щільності δCil імпульсного струму ip(t) часових форм, що розглядаються, у вказаних електричних
проводах і кабелях силових кіл ВСІТ. Отримані результати сприятимуть підвищенню електротермічної стійкості
електричних неізольованих проводів, а також ізольованих проводів і кабелів з ПВХ, Г і ПЕТ ізоляцією, які широко застосовуються в силових колах ВСІТ Purpose. Implementation of calculation choice of sections of electric wires and cables in circuits of devices of high-voltage highcurrent impulse technique (HHIT), characterized flowing of pulsed
current ip(t) with different amplitude-temporal parameters (ATP).
Methodology. Electrophysics bases of technique of high-voltage
and high pulsed currents, theoretical bases of the electrical engineering, bases of electrical power engineering, technique of high
electric and magnetic fields, and also measuring technique. Results.
The results of the developed generalized electrical engineering
investigations are resulted in a calculation choice on the condition
of thermal resistibility of cable products of boundary permissible
sections SCil of the electric uninsulated wires, and also insulated
wires and cables with copper (aluminum) cores (shells) with polyvinyl chloride (PVC), rubber (R) and polyethylene (PET) insulation,
on which in the circuits of HHIT the axial-flow of pulsed current
ip(t) flows with arbitrary ATP. On the basis of this approach the
results of concrete choice of sections SCil are presented for the indicated electric wires (cables) of power circuits of HHIT with pulsed
current, ATP of which with amplitudes of Imp=(0.1-1000) кА change
on an aperiodic law or law of damped sinusoid in nanо-, micro- and
millisecond temporal ranges. The results of calculation estimation
present maximum permissible approximations of δCil of pulsed current ip(t) of the examined temporal shapes in the indicated electric
wires and cables of power circuits of HHIT. It is shown that the
values of current approximations of δCil for the uninsulated copper
(aluminum) wires in the nanosecond temporal range of ATP of
pulsed currents ip(t) are about 495 (293) kA/mm2
, in the microsecond temporal range – 26 (15) kA/mm2
and in a millisecond temporal range – 543 (320) A/mm2. By a calculation it is set that for the
insulated wires (cables) with copper (aluminum) cores (shells) and
PET with insulation the indicated current approximation of δCil is
approximately: for the nanosecond range – 361 (233) kA/mm2
; for
the microsecond range – 19 (12) kA/mm2
; for the millisecond range
– 396 (256) A/mm2
. Originality. Firstly by a calculation for the
concrete temporal shapes of pulses of current ip(t) in the discharge
circuits of HHIT, changing in the wide range of the amplitudes Imp
on a aperiodic law or law of damped sinusoid, the numeral values
of cross-sections SCil and current approximations of δCil are obtained for the uninsulated wires, insulated wires and cables with
copper (aluminum) cores (shells) with PVC, R and PET insulation.
Practical value. Application in practice of model tests of objects of
electrical power engineering, aviation and space-rocket technique
on resistibility to direct action of pulsed currents ip(t) with different
ATP of natural (currents of lightning) and artificial (discharge currents of HHIT) origin to increase electro-thermal resistibility of the
electric uninsulated wires, and also the insulated wires and cables
with PVC, R and PET insulation of HHIT widely applied in power
circuits